Smaller keys for McEliece cryptosystems using convolutional encoders - Sebastião, Cláudia Maria Ferreira (2022)
The arrival of the quantum computing era is a real threat to the confidentiality and integrity of digital communications. So, it is urgent to develop alternative cryptographic techniques that are resilient to quantum computing. This is the goal of pos-quantum cryptography. The code-based cryptosystem called Classical McEliece Cryptosystem remains one of the most promising postquantum alternatives. However, the main drawback of this system is that the public key is much larger than in the other alternatives. In this thesis we study the algebraic properties of this type of cryptosystems and present a new variant that uses a convolutional encoder to mask the so-called Generalized Reed- Solomon code. We conduct a cryptanalysis of this new variant to show that high levels of security can be achieved using significant smaller keys than in the existing variants of the McEliece scheme. We illustrate the advantages of the proposed cryptosystem by presenting several practical examples.